Pengaruh Struktur Modal dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening - Fitri Amelia; Muhammad Anhar (Jurnal Ekonomi, 2019)
The purpose of this study was to determine whether the capital structure and growth of the company significantly affect the value of the company with profitability as an intervening variable in mining companies listed on the Indonesia Stock Exchange 2013-2017. Capital structure is proxied using the Debt-to-Equity Ratio (DER), Company growth is proxied using the calculation of Changes in Total Assets, Profitability is proxied using Return On Equity (ROE) and Company Value is proxied using Price to Book Value (PBV). By using purposive sampling technique, the sample used in this study amounted to 33 companies from a population of 41 companies and the research period was 5 years. This causal-comparative research uses panel data with documentation or archive data collection techniques from the Indonesian Capital Market Electronic Library. The analysis technique in this study uses Path Analysis. This study shows the results that capital structure has a significant effect on profitability and firm value, firm growth has no significant effect on profitability and firm value and profitability has no significant effect on firm value. Then Profitability is not able to mediate the effect of Capital Structure on Firm Value, but is able to mediate the effect of Company Growth on Firm Value